Determining the key elements in maintenance planning of the Masjid Kariah in Malaysian perspective / Azhar Yusof, Mohammad Ridzuan Yahya and Mohd Saidin Misnan - Yusof, Azhar; Yahya, Mohammad Ridzuan; Misnan, Mohd Saidin (UiTM Press, 2025)
In Malaysia, mosques encounter various maintenance-related challenges including limited financial resources, a shortage of skilled labour, and the necessity to reconcile traditional architectural and design elements with modern building techniques specifically for Masjid Kariah. Non-existence of formal measurement criteria for efficient Masjid Kariah maintenance planning has led to the aim of this study, which was to determine the key elements in maintenance planning of the Masjid Kariah in a Malaysian perspective. The qualitative approach was employed in this study through a Delphi survey where semi-structured interviews were conducted to 11 experts from academicians, maintenance practitioners and governments' sectors. The formation of conceptual framework through reviewing previous studies has helped the identification of the key elements. Thus, the results revealed that all 11 experts have been agreed and validated establishing 10 key elements in maintenance planning, which are Planned Preventive Maintenance, Planned Corrective Maintenance, Corrective Maintenance, Organisation Management, Planning and Scheduling, Financial Provision, Service Quality, Assessment, Resources Allocation and Safety and Health specifically for the Masjid Kariah. Hence, the stakeholders can develop a holistic maintenance planning based on those 10 key elements for Masjid Kariah. In conclusion, the combination between maintenance strategy and maintenance performance measurement can foster a good practice for maintenance planning.